A Critical Qualitative Study of the Position of Middle Managers in Health Care Quality Improvement. Issue 2 (April 2017) - Dainty, Katie N.; Sinclair, Douglas
Abstract : To date, health care quality improvement (QI) has focused on the engagement of executive leadership and frontline staff as key factors for success. Little work has been done on understanding how mid-level unit/program managers perceive their role in QI and how capacity could be built at this level to increase success. We present ethnographic data on the experience of hospital middle managers to consider how the expectations and capacity of their current position might influence QI progress organizationally. Abstract : Supplemental Digital Content is Available in the Text.